PENGETAHUAN IBU TENTANG IKAN DAN POLA KONSUMSI IKAN PADA BALITA DI DESA KEDONGANAN KABUPATEN BADUNG - Putu Febrina Ambara Dewi; I G. A. Ari Widarti; Desak Putu Sukraniti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Abstract. Fish is a good source of protein for toddlers.  Fish contains vitamins and minerals that are useful for the growth development.  Mother’s knowledge will affect the provision of meals for family members especially toddlers.  If mother’s knowledge is good, it will affect the selection, type of meal and frequency of meal comsumption.  This observational study was carried out using sross-sectional design.  Subject of the study were 61 mothers who had children under 5 years old in Desa Kedonganan Kabupaten Badung. Samples were taken using simple random sampling technique.  The results showed the majority of the samples (34,4%)  good knowledge about fish, moderate category (50,8%) sampels, and low category (14,8%).  The type of fish consumed in Desa Kedonganan was a type of sea fish 50 samples (82,1%).  The average amount of fish protein intake in toddlers is 14,52 grams per day.  The majority of the samples (52,5%) had low category and another of them have a good category (47,5%).     The  frequency  of fish comsumption in  toddlers  are majority samples (70,5%) often consumption fish.  Keywords : mother’s knowledge, consumption patterns